2020
DOI: 10.1089/can.2019.0099
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids Commonly Found in Cannabis sativa Do Not Modulate the Actions of Phytocannabinoids or Endocannabinoids on TRPA1 and TRPV1 Channels

Abstract: Introduction: Cannabis sativa produces hundreds of bioactive compounds, including cannabinoids and terpenoids. It has been proposed that cannabinoids act in synergy with terpenoids to produce the entourage effect, a concept used to explain the therapeutic benefits of medicinal cannabis. One molecular explanation for the entourage effect is that the terpenoids augment the actions of cannabinoids at their molecular drug targets in cells. We recently reported that terpenoids commonly found in cannabis do not infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Further studies need to be conducted to determine the exact EC 50 value of β-myrcene at the TRPA1 channels, but this was beyond the scope of our present study. The only study investigating the "entourage effect" of terpenoids modulating the action of cannabinoids tested 10 µM of β-myrcene on hTRPA1-expressing HEK293 cells [84]. We found that a minimum dose of 125 µM was required to elicit significant increases in [Ca 2+ ] i through rTRPA1 channels in our heterologous cell expression system.…”
Section: Discussionmentioning
confidence: 84%
“…Further studies need to be conducted to determine the exact EC 50 value of β-myrcene at the TRPA1 channels, but this was beyond the scope of our present study. The only study investigating the "entourage effect" of terpenoids modulating the action of cannabinoids tested 10 µM of β-myrcene on hTRPA1-expressing HEK293 cells [84]. We found that a minimum dose of 125 µM was required to elicit significant increases in [Ca 2+ ] i through rTRPA1 channels in our heterologous cell expression system.…”
Section: Discussionmentioning
confidence: 84%
“… 60 However, experimental studies have consistently failed to provide evidence for such an effect. 61 64 Nevertheless, the concept of the ‘entourage effect’ remains popular and is used to promote the health benefits of OTC supplements. 65…”
Section: Excipients Cannabis Oils and The Entourage Hypothesismentioning
confidence: 99%
“…Along with their role in photosynthesis, respiration, and plant defense, terpenoids are responsible for the flavor and aroma of different cannabis varieties and are considered as a major crucial factor of preference of the cannabis users. The therapeutic benefit of medicinal cannabis is that to produce a retinue effect, cannabinoids may function in synergy with terpenoids [ 49 ]. Over one hundred monoterpenes and sesquiterpenes have been identified in cannabis [ 50 ].…”
Section: Terpenoidsmentioning
confidence: 99%